Cerebral oximetry and postoperative delirium after cardiac surgery: a randomised, controlled trial1. (22nd September 2017) - Lei, L.; Katznelson, R.; Fedorko, L.; Carroll, J.; Poonawala, H.; Machina, M.; Styra, R.; Rao, V.; Djaiani, G.
Summary: Postoperative delirium is associated with increased morbidity and mortality. We hypothesised that restoration of regional cerebral oxygen desaturation would reduce the incidence of postoperative delirium in elderly patients after cardiac surgery. After institutional ethics review board approval and informed consent, a double‐blinded, prospective, randomised, controlled trial was conducted in patients ≥ 60 years of age undergoing cardiac surgery with cardiopulmonary bypass. In the intervention group, an algorithm was commenced if regional cerebral oxygen saturation decreased below 75% of baseline value for 1 min or longer. In the control group, the cerebral oximetry monitor screen was electronically blinded. Assessment of delirium was performed with confusion assessment method for intensive care unit or confusion assessment method after discharge from intensive care unit at 12‐h intervals for seven postoperative days. Postoperative delirium was present in 30 out of 123 (24.4%) and 31 out of 126 (24.6%) patients in the intervention and control groups, respectively, odds ratio 0.98 (95%CI 0.55–1.76), p = 0.97. Postoperative delirium was present in 20 (71%) out of 28 and in 41 (18%) out of 221 patients with baseline regional cerebral oxygen saturation ≤ 50, or > 50%, respectively, p = 0.0001. Higher baseline regional cerebral oxygen saturation and body mass index were protective against postoperative delirium. Restoration of regional cerebral oxygen desaturation did not result in lower postoperative delirium after cardiac surgery. Pre‐operative regional cerebral oxygen saturation ≤ 50% was associated with increased postoperative delirium rates in elderly patients following cardiac surgery.